SCHOOL INCLUSION OF CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) - Bianchi, Vilma Aparecida (2023)
The autistic should not be understood as someone who cannot learn, but as a person who has different ways of achieving this learning. Among the characteristics of the disorder, it can be mentioned: impairment in social interactions, deficiencies in verbal and non-verbal communication and limitation of activities and interests. The objective of the present work is to understand how the school inclusion of an autistic child can help them to socialize without discrimination. The methodology used to carry out this work was a literature review. Scientific articles found in databases such as: SciELO, ERIC, Educ@ and Periódicos Portal Capes were used. Scientific works appropriate to the theme, made available in Portuguese between the years 2002 to 2022, were selected. The inclusion of autistic children must go far beyond their presence in the classroom, it must aim, above all, at learning and developing skills and potential, overcoming difficulties. The inclusion of autistic children in regular classes cannot be synonymous with enrollment . It is essential that public policies seek, as a first step, to give priority to adequate and continuous training for teachers. Without this action, no pedagogical intervention will be possible.